2016
DOI: 10.1111/jth.13191
|View full text |Cite
|
Sign up to set email alerts
|

Actions of thrombin in the interstitium

Abstract: Summary. Thrombin is a pleiotropic enzyme best known for its contribution to fibrin formation and platelet aggregation during vascular hemostasis. There is increasing evidence to suggest a role for thrombin in the development of interstitial fibrosis, but interstitial thrombin has not been demonstrated by the direct determination of activity. Rather its presence is inferred by products of thrombin action such as fibrin and activated fibroblasts. This review will focus on possible mechanisms of thrombin formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…47 Thrombin may also activate proteolytic enzymes that degrade interstitium and extracellular matrix. 48 Fibrinogen (and its polymerized version fibrin) may enter into the brain and limit tissue repair. 49 All these blood-derived molecules would maintain a neuro-inflammatory status that may contribute to brain cells death.…”
Section: Hypothetical Biological Cascades Following the Onset Of Cmbsmentioning
confidence: 99%
“…47 Thrombin may also activate proteolytic enzymes that degrade interstitium and extracellular matrix. 48 Fibrinogen (and its polymerized version fibrin) may enter into the brain and limit tissue repair. 49 All these blood-derived molecules would maintain a neuro-inflammatory status that may contribute to brain cells death.…”
Section: Hypothetical Biological Cascades Following the Onset Of Cmbsmentioning
confidence: 99%
“…Whether these latter processes initiate or maintain AF is still unknown. Nevertheless, it has been reported that coagulation plays a key role in fibrosis [81,82], although this has never been investigated in relation to AF. PAR1 and PAR2 are both expressed by cardiomyocytes, and are involved in the proliferation of embryotic cardiac fibroblasts [83], suggesting a possible role of thrombin in the onset of AF.…”
Section: Effects Of Inhibition Of Thrombin On Cardiovascular Pathophymentioning
confidence: 99%
“…All these actions contribute to clot formation and maintenance. This enzyme yet has an anticoagulant function – thrombin activates protein C down-regulating the coagulation cascade [ 59 , 60 ].…”
Section: Enzyme Dysregulation Consequencesmentioning
confidence: 99%